Presentation - González Becerril, Juan Gabino (Papeles de Población; Vol. 24 Núm. 95 (2018): Papeles de Población, 2018)
Concern for the size of the population and its development has been a constant in mankind history. For example, United Nations in its proposals of the sustainable development goals for 2030, indicates that the world’s population at this moment is 7 600 million people, but at the same time it states that it will be 8 600 million by 2030. Moreover, in it projections it is stated that the population will be 9 800 by 2050 and 11 200 million by 2100. This same institution states that the ascending demographic process at global level at present and in the future will continue at a pace of about 83 million additional people every year, in spite of the constant diminution in the fertility levels.